Analysis of Operating Cash Flow (CFO) and Profit Management Using the Modified Jones Model in the Consumer Goods Industry towards Stock Prices in the Indonesia Stock Exchange, 2001-2020 - Farah Anisa; Pujiono Pujiono (Budapest International Research and Critics University, 2022)
This study aims to examine the usefulness of making decisions about the effect of operating cash flow and earnings management on stock prices in consumer goods industry companies according to conditions in 2001-2020 which are listed on the Indonesia Stock Exchange (IDX) through annual financial reports (Annual Report) and ICMD (Indonesian Capital Market Dictionary). Earnings management is carried out if the company takes advantage of the accounting policies of the consumer goods industry company. This study uses a modified Jones model approach in determining earnings management practices. Furthermore, the sampling technique used is purposive sampling and the data analysis technique uses SPSS to test multiple regression linear analysis. The results showed that operating cash flow had an effect on stock prices according to the year of research, while earnings management had no effect on stock prices. Thus, this research can be used by investors as an information in making investment decisions. The recommendation from this study is that further research can also distinguish pre-IFRS, IFRS transition and full IFRS years.